SIMPLICITY MEETS QUALITY: EXPLORING THE PATH TO CUSTOMER SATISFACTION IN DIGITAL TRANSPORTATION APPLICATIONS - Andine Herlina; Zakky Fahma Auliya (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The development of digital services in the transportation sector requires improvements in application quality to support user experience. This study aims to analyze the influence of perceived ease of use, e-service quality, and customer experience on customer satisfaction among users of the KAI Access application. A quantitative approach was used with a survey method through a questionnaire distributed to 85 respondents who were users of the application. Data analysis was performed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results show that all variables, namely perceived ease of use, e-service quality, and customer experience, have a positive and significant effect on customer satisfaction. Among the three, customer experience is the variable that has the greatest influence, indicating that user satisfaction is determined more by the holistic experience while using the application than by other technical aspects. E-service quality also plays an important role through system reliability, transaction security, and the accuracy of the information provided, while perceived ease of use has a smaller but still significant effect. These findings confirm that improving user experience and digital service quality should be prioritized in the development of digital transportation applications to increase user satisfaction and loyalty. This research addresses the limited attention given to post-usage behavior in digital transportation applications and offers an empirical contribution by applying Expectancy Disconfirmation Theory to explain customer satisfaction through perceived ease of use, e-service quality, and customer experience.